Revealing the mechanisms and therapeutic potential of immune checkpoint proteins across diverse protein families - Liu, Ran; Jiang, Xinyan; Dong, Ruijuan; Zhang, Yuting; Gai, Cong; Wei, Peng (Frontiers in Immunology, 2025)
Host immune responses to antigens are tightly regulated through the activation and inhibition of synergistic signaling networks that maintain homeostasis. Stimulatory checkpoint molecules initiate attacks on infected or tumor cells, while inhibitory molecules halt the immune response to prevent overreaction and self-injury. Multiple immune checkpoint proteins are grouped into families based on common structural domains or origins, yet the variability within and between these families remains largely unexplored. In this review, we discuss the current understanding of the mechanisms underlying the co-suppressive functions of CTLA-4, PD-1, and other prominent immune checkpoint pathways. Additionally, we examine the IgSF, PVR, TIM, SIRP, and TNF families, including key members such as TIGIT, LAG-3, VISTA, TIM-3, SIRPα, and OX40. We also highlight the unique dual role of VISTA and SIRPα in modulating immune responses under specific conditions, and explore potential immunotherapeutic pathways tailored to the distinct characteristics of different immune checkpoint proteins. These insights into the unique advantages of checkpoint proteins provide new directions for drug discovery, emphasizing that emerging immune checkpoint molecules could serve as targets for novel therapies in cancer, autoimmune diseases, infectious diseases, and transplant rejection.